Evolucao e perspectivas da geografia industrial no Brasil - Sampaio, S. S. (My University, 1988)
Tries to develop both an evolutional analysis and a critical appraisal of Brazilian industrial geography. This is a little-explored area in Brazil, as geographers have tended to focus on local and regional studies, rather than pursuing a holistic view of the national industrial system. Also notes the continuing dependence on the theoretical and methodological basis of work produced by capitalist developed countries. -from English summary
Brazilian industrial geography: evolution and perspectives
Keywords: industrial geography; national industrial system; Brazil